Design of E-Rent System with an Object Oriented Analysis and Design Method (Case Study at PT XYZ Rent) - Dinar Rahayu; Anwar Hilman; Benny Susanto; Yopi Nugraha (RISTEC : Research in Information Systems and Technology, 2021)
PT XYZ Tbk is the largest transportation rental service company in Indonesia. However, the process of submitting a lease from a customer still takes a long time and a lot of resources because it is done manually. It's very important for an organization to facilitate the business process with digitalization and to change physical files and documents to digital files (paperless) in the form of e-documents accompanied by e-digital signatures so that the process becomes faster, more effective and efficient. Therefore, this research purpose is to propose an E-Rent vehicle rental system to digitalize the current business processes. To determine the proposed design, research was conducted by analyzing user requirements, system requirements and conducting design modeling using the Object Oriented Analysis and Design method. Based on the result of the research conducted, it is expected the proposed system can meet the needs of the users in the vehicle rental process., both the users in the company and the customers.